Mendorong Semangat Inklusifisme dan Toleransi: Studi atas Buku Daras Pendidikan Agama Islam (PAI) dan Model Pembelajarannya di Universitas Brawijaya Malang - Media Zainul Bahri (Refleksi: Jurnal Kajian Agama dan Filsafat, 2019)
This article explores the insights of inclusivism and tolerance in Islamic religious education (PAI) textbooks in Brawijaya University (UB) Malang. This article is the result of research by reading textbooks, interviewing six PAI lecturers and focus group discussions (FGD) at UB Malang in December 2018. In general, there are many material aspects in the textbooks that encourage students to be open, respect for diversity and behave tolerant of different Islamic schools of thought. This is emphasized by the PAI lecturers since UB is a public university belong to the public and because in Islam itself there are many different understandings and schools of thought. The spirit of inclusivism, cosmopolitan and tolerance is seen explicitly in PAI UB’s textbooks and becomes the vision of PAI lecturers. If there is a deviation from the book tends to be a closed ideology, intolerant, and against the Republic of Indonesia, then it can be ascertained because of the “lecturer initiative” personally, and do not represent Lembaga Pusat Pembinaan Agama (the Central Institution of Religious Development).